Structural analysis of borotellurite glass - Mohamed Kamari, Halimah; Wan Yusoff, Wan Mohamad Daud; Ab. Aziz, Sidek; Sulaiman, Zainal Abidin; Hassan, Zainul Abidin; Hassan, Jumiah (Science Publications, 2007)
The average cross-link density, number of the network bonds per unit volume, average stretching force constant, atomic ring size and the ratio Kbc/Ke have been calculated and discussed according to bond compression model for borotellurite glass. The result showed that the connectivity and rigidity of the borotellurite glasses increases with TeO2 content due to the transformation of BO3 units to BO4 and TeO3 units to TeO4. Comparison between theoretical calculated and experimental elastic moduli and Poisson's ratio has been carried out. The results showed good agreement between experimental and theoretical calculated elastic moduli.